2020
DOI: 10.21203/rs.3.rs-39239/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike glycoprotein vaccine candidate NVX-CoV2373 elicits immunogenicity in baboons and protection in mice

Abstract: The COVID-19 pandemic continues to spread throughout the world with an urgent need for a safe and protective vaccine to effectuate herd immunity to control the spread of SARS-CoV-2. Here, we report the development of a SARS-CoV-2 subunit vaccine (NVX-CoV2373) produced from the full-length spike (S) protein, stabilized in the prefusion conformation. Purified NVX-CoV2373 S form 27.2 nm nanoparticles that are thermostable and bind with high affinity to the human angiotensin-converting enzyme 2 (hACE2) receptor. I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Alternatively, the loop that mediates inter-spike interactions may play a role in viral viability, consistent with our loop mutant data. Analysis of safety and immunogenicity of the Novavax SARS-CoV-2-3Q-2P-FL immunogen in mice and baboons revealed strong B-and T-cell responses to the vaccine with no evidence of vaccine-associated enhanced respiratory disease (VAERD) (15). Phase 1/2 clinical trial results showed that the vaccine induced immune responses exceeding levels seen in COVID-19 patients (31).…”
Section: S3 C To E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the loop that mediates inter-spike interactions may play a role in viral viability, consistent with our loop mutant data. Analysis of safety and immunogenicity of the Novavax SARS-CoV-2-3Q-2P-FL immunogen in mice and baboons revealed strong B-and T-cell responses to the vaccine with no evidence of vaccine-associated enhanced respiratory disease (VAERD) (15). Phase 1/2 clinical trial results showed that the vaccine induced immune responses exceeding levels seen in COVID-19 patients (31).…”
Section: S3 C To E)mentioning
confidence: 99%
“…Structural analysis of full-length SARS-CoV-2 spike protein from an advanced vaccine candidate 3Q-2P-FL immunogen to ACE2 by both bio-layer interferometry and ELISA clearly show binding to ACE2, indicating that the RBD is dynamic and the receptor binding site accessible (15). Another study on the prefusion structure of a full-length spike protein reported similar findings with RBDs clamped down as a consequence of potential clashes between S2 residues 828-853 and SD1 when RBD is in open conformation (16).…”
Section: Despite the Rbd-down Conformation Binding Analysis Of Thementioning
confidence: 99%
“…The spike ectodomain and full length spike formulations are important SARS-CoV-2 vaccine candidates (5,6,22) and it is therefore important to compare mRBD with these. We purified the Spike-2P stabilized ectodomain (Spike containing mutations K968P and V969P) protein from Expi293F cells by single step nickel chelate affinity chromatography followed by tag removal with a purified yield of ~25 mg/L culture (5).…”
Section: Rbd (332-532) Is More Highly Expressed and Thermotolerant Thmentioning
confidence: 99%
“…Over 150 vaccine candidates are under development globally (16). Some vaccine candidates that have entered rapidly into clinical phase testing include mRNA vaccine candidates by Moderna (mRNA-1273), BioNTech (BNT162b1) (17), and CureVac (CVnCoV), a Chimpanzee Adenovirus vector vaccine by University of Oxford and AstraZeneca (ChAdOx1-S) (18), a non-replicating adenovirus type-5 (Ad5) vaccine by Cansino (Ad5-nCoV) (19), a DNA vaccine by Inovio (INO-4800) (20), inactivated virus vaccines by Sinovac (PiCoVacc) (21) and Bharat Biotech (COVAXIN), a native like trimeric subunit spike protein vaccine by Clover Biopharmaceuticals /GSK/Dynavax (SCB-2019), and a full length recombinant glycoprotein nanoparticle vaccine by Novavax (NVX-CoV2373) (16,22). The majority of the above employ full length spike or the corresponding ectodomain as the antigen.…”
Section: Introductionmentioning
confidence: 99%
“…However, a substantial challenge of modelling vaccination against SARS-CoV-2 at this stage is the large number of unknown factors. At the time of writing, the UK has reportedly made deals for six different vaccine candidates created via differing approaches [3]: the Oxford (ChAdOx1 nCoV-19) [4,5] and Janssen (Ad26.COV2.S) [6] vaccines, made from a genetically engineered virus; a vaccine developed by BioNtech/Pfizer (BNT162b1) [7], which uses an novel approach of injecting part of the virus' genetic code; a vaccine created by Valneva (VLA2001) 1 [8], which uses an inactive version of the virus; a vaccine created by Novavax (NVX-CoV2373) [9] and one under development by GlaxoSmithKline/Sanofi Pasteur [10], both using protein adjuvants to stimulate an immune response.…”
Section: Introductionmentioning
confidence: 99%